2000
DOI: 10.1523/jneurosci.20-13-04776.2000
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Modulation of Exocytosis by Angiotensin II Involves Multiple G-Protein-Regulated Transduction Pathways in Chromaffin Cells

Abstract: Angiotensin II (AngII) receptors couple to a multitude of different types of G-proteins resulting in activation of numerous signaling pathways. In this study we examined the consequences of this promiscuous G-protein coupling on secretion. Chromaffin cells were voltage-clamped at -80 mV in perforated-patch configuration, and Ca(2+)-dependent exocytosis was evoked with brief voltage steps to +20 mV. Vesicle fusion was monitored by changes in membrane capacitance (DeltaC(m)), and released catecholamine was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 67 publications
5
47
1
Order By: Relevance
“…However, the involvement of AT 1 and AT 2 receptors in such effect is also dependent on the animal species studied [6][7][8][9][10][11][12]. It has been shown that cultured porcine chromaffin cells secreted catecholamines in response to an AT 2 agonist [9], whereas other studies have shown that Ang II increases catecholamine release from bovine chromaffin cells through functionally active AT 1 receptors [12]. Interestingly, some investigations reported mixed population of Ang II receptors in adrenal medulla depending on the species studied; for instance, AT 2 receptors accounted for 95% of Ang II binding sites in rat adrenal medulla, and 5% of the remaining binding sites were AT 1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of AT 1 and AT 2 receptors in such effect is also dependent on the animal species studied [6][7][8][9][10][11][12]. It has been shown that cultured porcine chromaffin cells secreted catecholamines in response to an AT 2 agonist [9], whereas other studies have shown that Ang II increases catecholamine release from bovine chromaffin cells through functionally active AT 1 receptors [12]. Interestingly, some investigations reported mixed population of Ang II receptors in adrenal medulla depending on the species studied; for instance, AT 2 receptors accounted for 95% of Ang II binding sites in rat adrenal medulla, and 5% of the remaining binding sites were AT 1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Early experiments demonstrated Ca 2+ influx through SOCCs upon ER Ca 2+ depletion of bovine chromaffin cells [23]; this was corroborated by later experiments [22,[24][25][26][27][28]. A direct proof for the presence of SOCCs was obtained from voltage-clamped bovine chromaffin cells where a small-amplitude, voltage-independent I CRAC carried by Ca 2+ and Na + , was characterised under conditions of Ca 2+ store depletion [29].…”
Section: Store-operated Calcium Channelsmentioning
confidence: 81%
“…Thus, histamine and angiotensin II stimulate exocytosis by a combination of ER Ca 2+ release and additional Ca 2+ entry through SOCCs [24]. More convincing evidence arises from experiments performed in voltage-clamped cells, where angiotensin II-induced exocytosis was associated with an uncharacterised leak current [27]. In addition, exocytosis could be elicited in the absence of depolarisation by photolysis of caged InsP 3 [31] or by bradykinin [32].…”
Section: Store-operated Calcium Channelsmentioning
confidence: 99%
“…Carbon-fibre amperometry provides a quantitative measure of oxidizable transmitter per release quantum, and has been increasingly used over the past two decades, for example, to characterize release of NA in chromaffin cells in real time (Travis & Wightman 1998;Teschemacher & Seward 2000).…”
Section: New Insights Into the Quantal Characteristics Of Noradrenalimentioning
confidence: 99%
“…The third hypothetical difference was that the excitatory effect of angiotensin II (AngII) on these neurons, or the characteristic AngII-induced Ca 2þ mobilization (Teschemacher & Seward 2000), may be enhanced in the SHR. Central AngII has been implicated in pathogenesis of excessive sympathetic activity and hypertension (at least in animal models) by numerous studies (Phillips et al 1977;Faber & Brody 1984;Itaya et al 1986;Wu & Berecek 1993) and it was, therefore, conceivable that stronger activation of CAergic neurons by central AngII could lead to a higher transmitter release in SHR.…”
Section: Altered Central Noradrenalin Signalling In An Animal Model Omentioning
confidence: 99%